Suporte informacional (aplicativo) de apoio aos usuários de crack, dependentes e codependentes: projeto Hope - Lucena, Maria Laura de Luna (2020)
This work results in the creation of an app with content regarding the use of crack cocaine by-product illicit drug. In addition to facilitating communication and interaction between groups of people who somehow need to deal with crack addiction, the application is also a producer and curator of relevant information on the topic, providing an important service to society, which still has difficulty. to deal with the matter clearly and without prejudice. There is also an important pedagogical function involved in the process, as the application has been produced and will be maintained by a team of students from technology as well as communication.Thus, the report brings notes on chemical dependence, crack use and abuse treated by Laranjeira (2010, 2012, 2014) and Oliveira e Correia and codependency by Melody (2017). It permeates digital journalism and its nuances through Castells' classic approach (put date); the important contribution of Silva (2008) dealing with the mobility of journalism and also the concept of digital networks of Recuero (2009; 2012). Service journalism was endorsed by authors Marques de Melo (2013), Vaz (2009) and Seixas (2013). Subsequently, it was the methodology that, in addition to the bibliographic review referenced above, worked the documentary review and the semi-structured interview.